Formação continuada de professores no ensino superior: a inserção das TIC na prática pedagógica dos docentes da Ufal - Silva, Guilmer Brito (2013)
The use of information technology and communication (ICT) in education set new pedagogical challenges for teachers, as well as the integration of these technologies has posed as a challenge for academics. In this context it is necessary to evaluate the contributions and limitations of continuous training for the use of ICT in higher education. This study was conducted during the development of institutional design, which occurred in 2011, to promote the use of ICT in undergraduate of the Federal University of Alagoas (Ufal). The questions guiding the research were: Training received contributed to teachers introduce ICT in their disciplines? And how was this integration?. This research aimed to examine the training of teachers to use ICT in higher education, describe the pedagogical proposals prepared by the teachers, in addition to identifying the possibilities and limitations of this process. The methodology used was collaborative action research with a qualitative approach. The data were collected by monitoring the training carried out observations of teaching plans prepared by teachers and construction disciplines of the virtual learning environment (VLE), in addition to the questionnaires. The subjects were teachers involved in the project. The results of the analysis show the importance and contributions of teacher training, indicate that distinct uses may occur on the part of teachers, integrating ICT in the teaching and identify the difficulties and weaknesses that occur in the process, enabling us to rethink pedagogical practice in training and reflect on the possibilities and difficulties of using ICT in higher education. Thus enabling new strategies for fostering teacher training to enable teachers to understand, develop and use ICT in their classes.